Ethnobotanical study of medicinal plants used in the treatment of post-harvest microbial diseases in strawberry and tomato crops in Morocco - Bessi, Aymane; Elhanafi, Laila; Rais, Chaimae; Slimani, Chaimae; Louafi, Boutaina; El Ghadraoui, Lahsen; Bouchamma, El Ouazna (Ethnobotany Research and Applications, 2025)
Background: People have long used medicinal and aromatic plants (MAPs) as part of an ethnobotanical tradition that combines health, food preservation and cultural heritage. In Morocco, local communities have exploited the natural antibacterial and antioxidant properties of these plants to prevent fruit and vegetables from spoiling and extend their shelf life. This ancestral knowledge, passed down from generation to generation, demonstrates a deep understanding of the functional value of local plants. Recent scientific research is beginning to confirm the validity of these traditional practices and reveal that many medicinal and aromatic plants commonly used by Moroccans, contain highly preservative bioactive compounds. Methods: In this context, a survey was conducted across three regions in Morocco, involving 250 participants who provided insights via questionnaires on potential MAPs with bio preservative characteristics. The data was analysed using SPSS software, with the chi-square test being applied to assess differences in plant use, preparation methods, and application techniques. JMP Pro version 17 software was used to analyse the contingency of the relationships between the profession of the respondents and the types of protection used, as well as multiple correspondence analysis to study the relationships between the identified plant species and the parts of the plants used. Quantitative ethnobotanical indices, including Use Value (UV), Family Use Value (FUV) and Fidelity Level (FL), were applied. Results: Lamiaceae family, particularly rosemary, emerged as the most prominent, with FUV = 27.8, UV =0.24 and FL = 100. Leaves were identified as the primary source of bioactive compounds, with essential oils and hydrolats being the most utilized forms. Conclusion: The study underscores the potential of MAPs as eco-friendly bio-preservatives for post-harvest food protection, especially plant species belonging to Lamiaceae family. Keywords: Medicinal and Aromatic Plants in Morocco, Ethnobotanical study, Tomato, Strawberry, Post-harvest food preservation.